SELF-INJURY IN EARLY ADULTHOOD IN ISLAMIC FAMILIES EXPERIENCING A BROKEN HOME (PSYCHOLOGY & MENTAL HEALTH) - Hammada, Basrul Akmal; Rusyid Affandi, Ghozali (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to analyze the relationship between emotional regulation, family background, and self-injury tendencies among young adults from Islamic broken-home families. Method: While self-injury has been widely studied, research focusing on young adults from broken-home families in Islamic communities remains scarce. Family background plays a crucial role in shaping emotional resilience, yet little is known about how these individuals regulate emotions and seek social support. Existing studies lack specific insights into the impact of emotional regulation, social support, and coping strategies on self-injury within this demographic. Results: The findings reveal that individuals with poor emotional regulation and lack of family support are more likely to engage in self-injury. Conversely, those with strong coping mechanisms and positive social interactions demonstrate better emotional well-being. Novelty: This research provides new insights into the cultural and familial influences on self-injury, filling a gap in the literature. The study underscores the need for psychological support, family counseling, and social interventions to reduce self-injury risks among vulnerable individuals.